1994
DOI: 10.1002/1097-0142(19941015)74:8<2245::aid-cncr2820740807>3.0.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

Tumor angiogenesis in human lung adenocarcinoma

Abstract: Background. Hematogenous metastasis requires angiogenesis within the tumor. Previous studies have shown that microvessel counts in histologic sections of the primary tumor, which reflect angiogenesis, are correlated with metastasis in breast, prostate and Stage I nonsmall cell lung carcinoma. In this study, the authors investigated the association between angiogenesis, hematogenous metastasis and lymph node metastasis in all stages of lung adenocarcinoma. Methods. Microvessels were highlighted by immunostainin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
69
1
2

Year Published

1996
1996
2002
2002

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(80 citation statements)
references
References 20 publications
7
69
1
2
Order By: Relevance
“…Microvessel density has been shown to be an independent parameter of the severity of tumour disease and a predictor of prognosis of breast cancer patients in most but not all studies addressing this issue (Weidner et al, 1991(Weidner et al, , 1992Bosari et al, 1992;Horak et al, 1992;Toi et al, 1993, Axelsson et al, 1995. A similar correlation has also been demonstrated with other human malignancies, including head and neck squamous cell carcinoma (Gasparini et al, 1993), lung adenocarcinoma (Yamazaki et al, 1994), rectal carcinoma (Saclarides et al, 1994), testicular germ cell tumours (Olivarez et al, 1994), prostate cancer , tumours of the oral cavity (Williams et al, 1994) and gastric carcinoma (Maeda et al, 1995 rie receptor in breast cancer P Salven et al higher when staining was performed using the clone 7E8 antibody (Table I). No specific staining was observed when the sections were incubated with antigen-blocked antibody instead of the primary antibodies, or with the peroxidaseconjugated secondary antibody only.…”
mentioning
confidence: 78%
“…Microvessel density has been shown to be an independent parameter of the severity of tumour disease and a predictor of prognosis of breast cancer patients in most but not all studies addressing this issue (Weidner et al, 1991(Weidner et al, , 1992Bosari et al, 1992;Horak et al, 1992;Toi et al, 1993, Axelsson et al, 1995. A similar correlation has also been demonstrated with other human malignancies, including head and neck squamous cell carcinoma (Gasparini et al, 1993), lung adenocarcinoma (Yamazaki et al, 1994), rectal carcinoma (Saclarides et al, 1994), testicular germ cell tumours (Olivarez et al, 1994), prostate cancer , tumours of the oral cavity (Williams et al, 1994) and gastric carcinoma (Maeda et al, 1995 rie receptor in breast cancer P Salven et al higher when staining was performed using the clone 7E8 antibody (Table I). No specific staining was observed when the sections were incubated with antigen-blocked antibody instead of the primary antibodies, or with the peroxidaseconjugated secondary antibody only.…”
mentioning
confidence: 78%
“…Generally speaking, neovascularity assessed by the microvessel counting in the tumour tissue has a prognostic value in a variety of cancers (Yamazaki et al, 1994;Maeda et al, 1995;Brawer, 1996;Gasparini et al, 1996;Takabayashi et al, 1996). In addition, the density of microvessels was not correlated with the tissue VEGF concentration measured by ELISA in soft tissue sarcomas.…”
Section: Discussionmentioning
confidence: 98%
“…Several reports have demonstrated a positive correlation between an increased number of new vessels and the development of metastasis (Gimbrone et al, 1974;Liotta et al, 1974;Liotta et al, 1991). It has been reported that neovasularity assessed by intratumoral microvessel density (MVD) correlates with clinicopathologic factors and the prognosis of a variety of cancers (Yamazaki et al, 1994;Maeda et al, 1995;Brawer, 1996;Gasparini et al, 1996;Takabayashi et al, 1996).…”
mentioning
confidence: 99%
“…In the 14 remaining eligible studies (Macchiarini et al, 1994;Yamazaki et al, 1994;Fontanini et al, 1995;Mattern et al, 1995;Chandrachud et al, 1997;Giatromanolaki et al, 1997;Takanami et al, 1997;Duarte et al, 1998;Imoto et al, 1998;Aikawa et al, 1999;D'Amico et al, 1999;Ohta et al, 1999;Sheng et al, 2000;Yano et al, 2000), published between 1994 and 2000, the total number of patients was 1866 ranging from 28 to 408. The main characteristics of these 14 studies are shown in Table 1.…”
Section: Studies Selection and Characteristicsmentioning
confidence: 99%